Forensically aware offenders and homicide investigations: challenges, opportunities and impacts. (29th July 2019) - Ferguson, Claire
ABSTRACT: Offender forensic awareness may negatively impact on an investigation. The detection avoidance behaviours of 22 police-trained murderers were examined. Offenders with forensic awareness appear to use many detection avoidance strategies depending on their relationship with the victim and whether they stage the crime scene. Common themes included body disposal; planning and making threats to kill; a history of deception; and interfering with the investigation.